(untitled) (Mustansiria Dental Journal, 2018)
The aim of this in vivo study was to compare the accuracy of apex locater in determination of working length during endodontic work with that of conventional radiograph. A total of 24 mandibular teeth in patients (40-60 years) were used in this study. Working length for each tooth was measured using root ZX apex locater and conventional radiography. Results of this study revealed that twenty one readings obtained by the apex locator were shorter than readings obtained by radiographs; two cases were the same readings and only one case in which the reading by apex locator was more than the reading by radiograph. In conclusion the electronic apex locater (EAL) can be used for estimation of the working length and it is almost as the same as the conventional radiographs but with an important advantage which is the less radiation hazards.